A Study of Mobile Phone Usage Among The Post Graduate Students - Bhatt, Mayank Vinodbhai (Indian Journal of Marketing, 2008)
Usage of mobile phone has increased among the students in the recent time. Rapid growth and competition among the mobile handset companies and mobile service provider companies have decreased the rates for mobile handsets as well as mobile services. This has resulted in the increase of customer base.Now a days we can find a mobile phone with every student. Thus it is of significant interest to assess the student’s view on usage, necessity and spending on mobile phones.However, to the best of our knowledge, there has not been any survey that exclusively compares the student’s perspective on the different mobile handset companies and mobile service providers.